RELEVANSI PROGRAM PEMBELAJARAN DI PONDOK PESANTREN NURUL HUDA KECAMATAN JAKENAN KABUPATEN PATI DAN PERKEMBANGAN MODERNISASI - Heni Mustaghfiroh (Tarbawi : Jurnal Pendidikan Islam, 2022)
The era is growing, technology is also advancing rapidly is a form of starting the era of modernization. A boarding school for the wider community is known for its teachings that are only about religion. In Islamic boarding schools, education takes place with a classical nature, therefore there are many public arguments that spread about the backwardness of modern knowledge in the Islamic boarding school environment. At first, pesantren was indeed a non-formal education that was only guided by Arabic-language books by previous Muslim leaders as teaching materials taught in routine learning. But along with the presence of progress and the number of smart and millennial new generations, they come with new ideas that are more modern in nature but still adhere to religious values. By conducting research and making the Nurul Huda Islamic boarding school as the object of research that the author takes, the aim is to find out how relevant it is if the Islamic boarding school with its famous classical and traditional nature is faced with the development of the current modernization era. For his writing, the author refers to the qualitative method with the reason to obtain valid data related to the research carried out at the Nurul Huda Islamic Boarding School.